PENGARUH MANAJEMEN KESISWAAN TERHADAP PRESTASI BELAJAR PESERTA DIDIK KELAS IX MAN 4 PIDIE JAYA - Abdullah Ali (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2022)
Learning outcomes are the main goals that must be achieved by learning activities. Learning outcomes are used to determine how well students understand and are able to understand the material. The achievement of student learning outcomes is related to cognitive, emotional, and psychomotor aspects. From this, it can be concluded that learning outcomes are abilities possessed by students after going through the learning process at school, related to their knowledge, and can be measured by measuring them in the form of numerical tests. Learning outcomes in the world of education are measured by assessments carried out after the learning process. The results of this study provide an overview of students' progress in participating in learning from time to time. The purpose of this study was to determine the effect of student management on the learning achievement of class IX students at MAN 4 Pidie Jaya. The populations in this study were students of class IX MAN 4 Pidie Jaya. The determination of the sample design used in this study was based on the purposive sampling method with 60 students obtained and then 35 students were drawn as samples. The data analysis method in this study uses simple linear regression to predict the effect of the independent variables. The results show that student management has a significant effect on learning achievement, which means student management also means the entire process of planned and considered activities, as well as continuous student development so that the learning process from student registration to withdrawal can be tracked effectively and efficiently.